2005
DOI: 10.1007/s11095-005-5276-6
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Iontophoretic Delivery of Vapreotide Acetate AcrossPorcine Skin in Vitro

Abstract: Based on the observed transport rate of vapreotide across porcine epidermis and its clinical pharmacokinetics, therapeutic concentrations should be achievable using a 15-cm2 patch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…The impact of electrical current on the stability of Cyt c solutions was evaluated prior to the iontophoretic permeation studies. 5 ml of unbuffered protein solution (8.7 mg.ml j1 (0.7 mM), typical concentration for the permeation studies, pH 8.2) was subjected to a current density of 0.5 mA.cm j2 using salt bridges (20). Samples were collected and analysed every hour for a period of 8 h. Experiments were performed in triplicate.…”
Section: Protein Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of electrical current on the stability of Cyt c solutions was evaluated prior to the iontophoretic permeation studies. 5 ml of unbuffered protein solution (8.7 mg.ml j1 (0.7 mM), typical concentration for the permeation studies, pH 8.2) was subjected to a current density of 0.5 mA.cm j2 using salt bridges (20). Samples were collected and analysed every hour for a period of 8 h. Experiments were performed in triplicate.…”
Section: Protein Stabilitymentioning
confidence: 99%
“…Dermatomed skin was clamped in threecompartment vertical flow-through diffusion cells (area 0.85 cm 2 ). The anode (containing PBS buffer at pH 7.4) was isolated from the donor solution via a salt bridge (SB) assembly (3% agarose in 0.1 M NaCl) to minimize the effect of competing ions (20). After a 40 min equilibration period with PBS, 1 ml of unbuffered peptide solution containing Cyt c (0.7 mM, pH 8.2) and ACE (15 mM) was placed in the donor compartment.…”
Section: Iontophoretic Permeationmentioning
confidence: 99%
“…I particularly recommend the superb 5-fluorouracil series summarized in figure 5[106], the work on the 5-aminolevulinic acid esters [109], and that on the relative contribution of electro-osmosis and electrorepulsion [21]. Later, the group provided further insight into transport numbers during transdermal iontophoresis [110,111,112,113], an aspect which had been relatively neglected in the field, and into peptide iontophoretic transport [114,115,116,117,118,119,120,121] presenting new structure-transport relationships. On the whole, the extensive work by Guy and collaborators provided a better understanding of drug iontophoretic transport and its rational optimization.…”
Section: Iontophoresismentioning
confidence: 99%
“…herpes labialis [71] and the local delivery of anti-oxdiants [72] ) and for systemic effect (e.g. migraine [73,74] and chemotherapy-induced emesis [75][76][77] ), therapeutic peptides (triptorelin and vapreotide), [78,79] and conducted mechanistic studies that resulted in the first published reports on the non-invasive transdermal delivery of functional proteins across the skin. [80][81][82][83] Experiments with valaciclovir, a cleavable valine ester prodrug of aciclovir with superior oral bioavailability, showed that its transdermal iontophoresis resulted in several hundred-fold increases in aciclovir delivery due to the charged amino group.…”
Section: Iontophoresis: Using Electricallyassisted Transport To Delivmentioning
confidence: 99%